Difficult cannulation: what should I do before EUS guided access? - Artifon, Everson L.A. (2017)
Selective cannulation of the common bile duct can be difficult, so multiple strategies have been developed to overcome the situation. In this review we analize the different strategies that can be used like different papillotome instead of the standard catheter, precut papillotomy using precut needle knives or precut papillotome, transpancreatic papillary septotomy, and stenting of the pancreatic duct. Bile duct cannulation remains an important benchmark of successful ERCP. Alternative biliary access indication and its use is very important If biliary cannulation remains unsuccessful.The suprapapillary puncture is a promissory technique. It´s important to have in mind that the goal of all techniques is to provide acute pancreatitis decrease.